2012
DOI: 10.3389/fnevo.2012.00004
|View full text |Cite
|
Sign up to set email alerts
|

The Language–Number Interface in the Brain: A Complex Parametric Study of Quantifiers and Quantities

Abstract: The neural bases for numerosity and language are of perennial interest. In monkeys, neural separation of numerical Estimation and numerical Comparison has been demonstrated. As linguistic and numerical knowledge can only be compared in humans, we used a new fMRI paradigm in an attempt to dissociate Estimation from Comparison, and at the same time uncover the neural relation between numerosity and language. We used complex stimuli: images depicting a proportion between quantities of blue and yellow circles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 48 publications
11
69
0
Order By: Relevance
“…Previous fMRI studies of quantifier comprehension have also consistently reported parietal cortex activation (McMillan et al, 2005; Troiani et al, 2009a; Heim et al, 2012) and patients with neurodegenerative disease in parietal cortex have difficulty with interpreting quantifier meaning (McMillan et al, 2005, 2006; Morgan et al, 2011; Troiani et al, 2009a). Together, these findings have been interpreted as evidence for the role of number knowledge contributing to quantifier comprehension.…”
Section: Discussionmentioning
confidence: 89%
“…Previous fMRI studies of quantifier comprehension have also consistently reported parietal cortex activation (McMillan et al, 2005; Troiani et al, 2009a; Heim et al, 2012) and patients with neurodegenerative disease in parietal cortex have difficulty with interpreting quantifier meaning (McMillan et al, 2005, 2006; Morgan et al, 2011; Troiani et al, 2009a). Together, these findings have been interpreted as evidence for the role of number knowledge contributing to quantifier comprehension.…”
Section: Discussionmentioning
confidence: 89%
“…Recently the value of including language as measure has been stressed in the prediction of numeracy development (Heim, Amunts, Drai, Eickhoff, Hautvast, & Grodzinksy, 2012;Purpura et al, 2011;Romano, Babchishin, Pagani, & Kohen, 2010;Sarnecka et al, 2007;Wiese, 2003). Oral language skills include receptive language, expressive language and the understanding of grammatical rules and the structure of language (Purpura et.…”
Section: Language In Kindergarten and Early Arithmeticmentioning
confidence: 99%
“…Previous experimental works Tomaszewicz 2011;Heim et al 2012) have shown that most is sensitive to Weber's law such that most statements are more difficult to verify in arrays with close blue:non-blue ratios compared to arrays in which the two numerosities are further apart. Experiment 1 showed that this result holds not only when the arrays are presented for very short durations but also when participants are given as much time as they need to make their decision.…”
Section: Discussionmentioning
confidence: 99%
“…We combined this with a WEBER RATIOS manipulation as used in Lidz et al (2011) but not in Kotek et al (2011a): under this manipulation, the relative sizes of the blue set and the non-blue set are varied. Verification of most statements has been shown by Lidz et al (2011) to be sensitive to Weber's law, stating that the discriminability of two quantities is a function of their ratio (see Pica et al 2004; see also Heim et al 2012, andTomaszewicz 2011 for relevant work on Polish). Specifically, Lidz et al (2011) showed that the accuracy of the verification of most statements increases gradually as the ratio of blue to non-blue dots in an array increases.…”
Section: Current Experimentsmentioning
confidence: 99%